PERANCANGAN SISTEM INFORMASI CUSTOMER COMPLAINT PADA PT ASTRA INTERNATIONAL DAIHATSU BERBASIS WEB DENGAN MENGGUNAKAN MODEL RAPID APPLICATION DEVELOPMENT - Frieyadie Frieyadie (LPPM Universitas Bina Sarana Informatika, 2013)
In doing service to customers at all branches throughout Indonesia, PT. Astra InternationalDaihatsu to use two-way services such as inbound and outbound. Inbound have a sense of wherethe company contacted customers to promote goods and services and also accepted if there arecomplaints from the customer for its vehicles. As for the outbound sense is customer conductcomplaint or complaints to Customer Care regarding issues facing the vehicle, either viatelephone or directly visit the service center at the nearest dealers The purpose of this paper is toprovide ease of control and the handling of problems customer facing and as for the aims andobjectives include: Fostering customer confidence on after sales service of PT Astra InternationalDaihatsu. Facilitate handling of the problems faced by the customer to quickly and precisely.Providing solutions in terms of processing the data of the customer in order to get accurate data.The model used in the design of customer complaint information system using rapid application model.Keywords: Information Systems, Customer Complain , Rapid Application Model